Effect of feed restriction on performance and feed digestibility in rabbits - A. Nizza (Italian Journal of Animal Science, 2010)
Two hundred and fifty-six Hyla rabbits were equally divided into two groups fed the same commercial concentrates supplied ad libitum (group AL) or restricted to 90 % of ad libitum (group RES) from weaning (35 d) to slaughter (85 d). Mortality was recorded daily. On 20 rabbits per group feed intake and live weight were recorded, respectively, on a daily and weekly basis. Samples of concentrates and faeces were collected and chemical composition and acid insoluble ashes were determined, the latter to estimate nutrient digestibility. The moderate feed restriction did not induce differences in slaughter weight (2755.3 vs 2732.2g, respectively for groups AL and RES) or in the average daily weight gains of the rabbits (40.02 vs 39.54 g/d, respectively for groups AL and RES) while the feed conversion ratios were more favourable for group RES (3.88 vs 3.40, respectively for AL and RES groups, P<0.05). The same rabbits showed significantly higher apparent digestibility for almost all the nutrients (except crude protein and ether extract) in particular for the crude fibre, NDF and ADF, confirming a higher residence time of the feeds in the digestive system.